2019
DOI: 10.1155/2019/7417239
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Complete Chloroplast Genome of Acer truncatum Bunge (Sapindales: Aceraceae): A New Woody Oil Tree Species Producing Nervonic Acid

Abstract: Acer truncatum, which is a new woody oil tree species, is an important ornamental and medicinal plant in China. To assess the genetic diversity and relationships of A. truncatum, we analyzed its complete chloroplast (cp) genome sequence. The A. truncatum cp genome comprises 156,492 bp, with the large single-copy, small single-copy, and inverted repeat (IR) regions consisting of 86,010, 18,050, and 26,216 bp, respectively. The A. truncatum cp genome contains 112 unique functional genes (i.e., 4 rRNA, 30 tRNA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 60 publications
4
21
0
Order By: Relevance
“…(2019) and Ma et al . (2019) proved that A. truncatum and A. miaotaiense are closely related. In our study, we found that A. truncatum was not only closely related to A. miaotaiense , but also to A. catalpifolium , based on phylogeny of the chloroplast genomes.…”
Section: Discussionmentioning
confidence: 98%
“…(2019) and Ma et al . (2019) proved that A. truncatum and A. miaotaiense are closely related. In our study, we found that A. truncatum was not only closely related to A. miaotaiense , but also to A. catalpifolium , based on phylogeny of the chloroplast genomes.…”
Section: Discussionmentioning
confidence: 98%
“…Eight to ten years to maturity Appelqvist, 1976;Jart, 1978;Taylor et al, 2009;Qiao et al, 2018;Ma et al, 2019Ma et al, , 2020 Xanthoceras its development and industrialization (Wang et al, 2006;Tang et al, 2013;Xu et al, 2019). T. speciosum, a unique perennial herbaceous plant species from Chile, has a seed oil content in the range of 12.3∼26.0%, with NA remarkably constituting 40.0∼45.4% of the total FA content.…”
Section: Na Resources From Plantsmentioning
confidence: 99%
“…Third, some seed oils require the removal of erucic or lignoceric acid by distillation or other expensive methods before they can be used in health applications. Therefore, although a number of species present excellent oil or NA contents, only L. annua and A. truncatum are considered niche species in practice (Ma et al, 2019(Ma et al, , 2020, and the other plant species must be further researched to address the current NA extraction inefficiencies. Genetic modification may thus be an excellent approach for the mass production of NA.…”
Section: Na Resources From Plantsmentioning
confidence: 99%
See 2 more Smart Citations